The media education in the EHEA - Aran-Ramspott, Sue (Historia y Comunicación Social, 2014)
The present study looked at the ability of students to correctly interpret relationships in serialized fictional television. The theoretical framework is from the work of the RETEVIS research group (Medina et al., 2008; Aran, Medina, Rodrigo, 2010), and defends a notion of media education (Buckingham, 2003), which exceeds the strict literal interpretation of audiovisual “grammar”. In the focus group, we observe both the effectiveness of media education in the development of analytical and critical discourse on stereotypes, as well as the possibilities of the EHEA as part of a university open to change within evolutionary contexts.
Keywords: Media education; fiction television; youth; love stereotypes; EHEA.